Être lesbienne, gay ou bisexuel·le dans une organisation française : le rôle des micro-agressions homonégatives et l’effet médiateur du climat de diversité sexuelle dans le choix de dévoiler ou dissimuler son orientation sexuelle - Grelier, Anaelle; Demarque, Christophe; Suchier, Johann; Dupoirier, Samuel (Pratiques psychologiques, 2021)
Les personnes lesbiennes, gaies et bisexuelles (LGB) peuvent mobiliser différentes stratégies pour dévoiler ou cacher leur orientation sexuelle sur leur lieu de travail. Cette étude a pour objectif d'explorer les relations entre les micro-agressions homonégatives (MAH) perçues au travail et ces stratégies, ainsi que l'effet médiateur du climat organisationnel de diversité sexuelle dans ces relations. Un échantillon de 135 salariés·e·s LGB a répondu à un questionnaire en ligne portant sur ces trois variables. Les données ont été traitées par le biais de régressions linéaires simples et de méthodes d'analyse en pistes causales. Les résultats ont mis en avant que l'effet des MAH sur la gestion de son identité sexuelle au travail était médiatisé par le climat de diversité sexuelle. Il existe également une relation directe positive entre les MAH et le dévoilement. Les résultats sont discutés à la lumière de la littérature existante sur le sujet. Des perspectives aux niveaux systémiques et individuels pour soutenir le climat de diversité sexuelle et réduire la discrimination vécue par les salarié·e·s LGB sont envisagées.
Number: 1
Keywords: discipline; europe; france; identités LGBTQIA2+; psychologie; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail; violences

Companion to sexuality studies - Naples, Nancy A. (Wiley Blackwell, 2020)
An inclusive and accessible resource on the interdisciplinary study of gender and sexuality Companion to Sexuality Studies explores the significant theories, concepts, themes, events, and debates of the interdisciplinary study of sexuality in a broad range of cultural, social, and political contexts. Bringing together essays by an international team of experts from diverse academic backgrounds, this comprehensive volume provides original insights and fresh perspectives on the history and institutional regulatory processes that socially construct sex and sexuality and examines the movements for social justice that advance sexual citizenship and reproductive rights. Detailed yet accessible chapters explore the intersection of sexuality studies and fields such as science, health, psychology, economics, environmental studies, and social movements over different periods of time and in different social and national contexts. Divided into five parts, the Companion first discusses the theoretical and methodological diversity of sexuality studies.Subsequent chapters address the fields of health, science and psychology, religion, education and the economy. They also include attention to sexuality as constructed in popular culture, as well as global activism, sexual citizenship, policy, and law. An essential overview and an important addition to scholarship in the field, this book: Draws on international, postcolonial, intersectional, and interdisciplinary insights from scholars working on sexuality studies around the world Provides a comprehensive overview of the field of sexuality studies Offers a diverse range of topics, themes, and perspectives from leading authorities Focuses on the study of sexuality from the late nineteenth century to the present Includes an overview of the history and academic institutionalization of sexuality studies The Companion to Sexuality Studies is an indispensable resource for scholars, researchers, instructors, and students in gender, sexuality, and feminist studies, interdisciplinary programs in cultural studies, international studies, and human rights, as well as disciplines such as anthropology, psychology, history, education, human geography, political science, and sociology.
Keywords: LGBTQIA2+; anthropologie; approches et analyses; cours; discipline; féminisme décolonial; premier cycle; psychologie; queer; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; thématiques; études de genres; études des sexualités